Philosophy as Saṃvāda and Svarāj: dialogical meditations on Daya Krishna and Ramchandra Gandhi - Mayaram, Shail (SAGE, 2014)
Some papers presented at a seminar held at Indian Institute of Advanced Study during 28-30 April 2008